Analysis Of Dynamics Of Business Environment And Their Impact On Human Resource Management (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Human resources have played a role in managing workplace complication as the business environment is continuously changing. The latest paper reviews the positive and negative impact on the organisation’s human resources resulting from the dynamics of technical, legal, political, and economic factors. The qualitative research technique applied in the study improves knowledge and systematically analyses resources. Research sheds light on how the technological environment, privatisation, globalisation, labour migration, changing social needs in the workplace and changing diversity affect the employees’ work. The research paper examines the business executive’s changing role in dealing with several human resource motivation activities and training to adapt changes to enhance competition effectively. Human resources are an indispensable organisational resource that needs to be adapted to changes to increase efficiency. Success and organisational efficiency depend on the knowledge, capability, and skills of human resources, which need to be reviewed and updated with a changing business environment. There is no loophole in achieving business success. The research paper noted a positive impact on organisational development owing to improved human resource talent competencies.